2016
DOI: 10.1177/0300060516665708
|View full text |Cite
|
Sign up to set email alerts
|

Segmental portal/superior mesenteric vein resection and reconstruction with the iliac vein after pancreatoduodenectomy

Abstract: ObjectiveThe results of segmental venous resection (VR) combined with pancreatoduodenectomy (PD) are controversial but may be promising. Few studies have described reconstruction of the portal/superior mesenteric vein (PV/SMV) with the iliac vein harvested from donation after cardiac death (DCD).MethodsFrom January 2014 to April 2016, PD combined with segmental excision of the PV/SMV (VR group) was performed in 21 patients with adenocarcinoma of the head of the pancreas (ADHP). The authors established a new te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The PRISMA flow diagram for systematic review is presented in Figure 1 . Twenty-three studies comparing PD+VR and standard PD for patients with PHAC, published between May 1998 and November 2019, were considered suitable for the meta-analysis [ 8 , 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. On review of the data extraction, there was 100% agreement between the three reviewers.…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow diagram for systematic review is presented in Figure 1 . Twenty-three studies comparing PD+VR and standard PD for patients with PHAC, published between May 1998 and November 2019, were considered suitable for the meta-analysis [ 8 , 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. On review of the data extraction, there was 100% agreement between the three reviewers.…”
Section: Resultsmentioning
confidence: 99%
“…Data on duration of surgery were available in 11 (13,17,21,23,28,30,37,43,44,46,47) of 41 studies which demonstrated a prolonged operating time in patients with VR. The mean operating time was 491 minutes (ranging from 342 to 667) for patients undergoing pancreatectomy with VR, compared to 399 minutes (ranging from 306 to 568) for patients without VR (P<0.00001).…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…The mean operating time was 491 minutes (ranging from 342 to 667) for patients undergoing pancreatectomy with VR, compared to 399 minutes (ranging from 306 to 568) for patients without VR (P<0.00001). Meanwhile, data on blood loss during operation was available only in 8 studies (17,21,23,28,34,37,44,46). The average blood loss in the VR+ group was 929 mL (ranging from 343 to 1,686) and in the VR− group 581 mL (ranging from 353 to 866), indicating VR with increased blood loss (P=0.0001).…”
Section: Perioperative Outcomesmentioning
confidence: 99%
See 2 more Smart Citations